Challenging Islamist Populism in Indonesia through Catholic Youth Activism - Nilan, Pam (Religions, 2021)
This paper reports data from a study of young Catholic activists. They were concerned about the expansion of Islamist populism in democratic Muslim-majority Indonesia. They actively built inter-faith coalitions with local liberal Muslim youth groups and with pan-national Nahdlatul Ulama (NU), the largest independent Islamic organisation in the world. Islamist populism prioritises religious identity over the national identity of citizenship. In framing their citizenship activism against the current tide of Islamist populism, the informants in our study selectively engaged aspects of Catholic theology. They articulated their religious identity as coterminous with a nationalist identity centred on multi-faith tolerance and harmony. That discourse in itself refutes a key principle of Islamist populism in Indonesia, which argues for primordial entitlement.